PENERAPAN SANKSI HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA NARKOTIKA DI WILAYAH HUKUM KEPOLISIAN RESORT KOTA YOGYAKARTA - Agung Noviantoro; Suryawan Raharjo (Kajian Hasil Penelitian Hukum, 2022)
Abstract This thesis aims to review and analyze the application of the law against children of narcotics offenders in the jurisdiction of the Yogyakarta City Resort Police and review and analyze the factors that affect the application of the law to children of narcotics offenders and how to countermeasures. Used type of research is normative juridical with conceptual, statutory and case approaches. The method of analcys is qualitative descriptive. Research result was Yogyakarta City Resort Police applied the law to the children of narcotics offenders by applying Diversion in reference to Law Number 11 of 2012 on the Juvenile Criminal Justice System. Diversion stage with mediation and deliberation with related elements. Factors that affect the application of the law to children of narcotics offenders include internal and external factors. Internal factors (Law enforcement officers and facilities), while for external factors (There are no implementing rules on Diversion, Society and culture). As for the efforts made to overcome these obstacles can be done, namely: Increasing understanding of the concept of diversion that is fair restorative; Increased education; Providing personality training; Have to make a change.